The population structure of two sympatric hermit-crab species on a subtidal rocky shore of an island in southeastern Brazil - DANIEL J.M. LIMA; VALTER J. COBO; MARIANA A.B. DE AQUINO; ADILSON FRANSOZO (Anais da Academia Brasileira de Ciências, 2014)
The main goal of this investigation was to characterize the population structure and shell occupancy of two sympatric hermit-crab species, Pagurus brevidactylus and Paguristes tortugae. The study was undertaken at Couves Island on the southeastern coast of Brazil, from March 2010 through February 2011, on subtidal rocky bottoms. Specimens were collected by SCUBA diving sessions. A total of 195 individuals of P. brevidactylus and 132 of P. tortugae were examined. Both populations showed unimodal size-frequency distributions, which were non-normal for P. brevidactylus and normal for P. tortugae. The median size of P. brevidactylus was significantly smaller than P. tortugae; in both species, males were significantly larger than females. For both, juveniles and ovigerous females were recorded in all size classes and in almost the entire sampling period. No significant departures from the 1:1 sex ratio were detected, although some size classes were skewed. Overlaps in shell occupation were recorded. Pagurus brevidactylus and P. tortugae showed similar population features; they reached sexual maturity at small sizes, and the nearly year-round presence of young and ovigerous females suggests continuous reproduction. These inter-specific interactions involving resource partitioning suggest a regulatory process that is probably part of the equilibrium strategy of these populations.